TARIAN ADAT KABASARAN DI MINAHASA (ANALISIS NILAI BUDAYA DAN PELUANGNYA SEBAGAI SUMBER PENDIDIKAN KARAKTER) - Rahman, Eka Yuliana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to analyze how traditional Minahasa dances can be used as a source of character education, through an analytical approach to cultural values. This study uses a qualitative method, because it is a procedure that produces descriptive data in the form of written or oral data in the Minahasa community. It is also supported by an ethnographic method that focuses on personal experience, and participation born from the field observation process. The results of the research that become cultural values as a source of character education are building Minahasa identity such as courage, agility, valor and especially togetherness. This can be seen in the character of the dancer who is hard, disciplined and firm, mirrors the attitude of uniting and unifying each other, the attitude of chivalry and soldiering. The dancers wear red Minahasa woven clothes and make-up that looks firm and full of authority and has an attitude of courage